CRATERING AND MODIFICATION OF WET-TARGET CRATERS: PROJECTILE IMPACT EXPERIMENTS AND FIELD OBSERVATIONS OF THE LOCKNE MARINE-TARGET CRATER (SWEDEN) - Ormö J.; Lepinette A.; Martinez-Frias J.; Lindström M.; Diaz-Martinez E. (My University, 2006)
Marine impacts are one category of crater formation in volatile targets. At target water depths exceeding the diameter of the impactor, the zones of vaporization, melting, and excavation of the standard land-target cratering model develop partially or entirely in the water column. The part of the crater that has a potential of being preserved (seafloor crater) may to a great extent be formed by material emplacement and excavation processes that are very different from land-target craters. These processes include a high-energy, water-jet-driven excavation flow. At greater water depths, the difference in strength of the target layers causes a concentric rater to evolve. The crater consists of a wide water cavity with a shallow excavation flow along the seabed surrounding a nested, deeper crater in the basement. The modification of the crater is likewise influenced by the water through its forceful resurge to fill the cavity in the water mass and the seafloor. The resurge flow is strongly erosive and incorporates both ejecta and rip-up material from the seabed surrounding the excavated crater. A combination of field observations and impact experiments has helped us analyze the processes affecting the zone between the basement crater and the maximum extent of the water cavity. the resurge erosion is facilitated by fragmentation of the upper parts of the solid target caused by a) spallation and b) vibrations from the shallow excavation flow and, subsequently, c) the vertical collapse of the water cavity rim wall. In addition, poorly consolidated and saturated sediments may collapse extensively, possibly aided by a violent expansion of the pore water volume when it turns into a spray during passage of the rarefaction wave. This process may also occur at impacts into water-saturated targets without an upper layer of seawater present. Our results have implications for impacts on both Earth and Mars, and possibly anywhere in the solar system where volatiles exist/have existed in the upper part of the target. © The Meteoritical Society, 2006.